Influences of semantic and syntactic context on open- and closed-class words - Van Petten, Cyma; Kutas, Marta (Memory & cognition, 1991)
Event-related potentials (ERPs) were recorded as subjects read semantically meaningful, syntactically legal but nonsensical and random word strings. The constraints imposed by formal sentence structure alone did not reduce the amplitude of the N400 component elicited by open-class words, whereas semantic constraints did. Semantic constraints also eliminated the word-frequency effect of a larger N400 for low-frequency words. Responses to closed-class words exhibited reduced N400 amplitudes in syntactic and congruent sentences, indicating that formal sentence structure placed greater restrictions on closed-class words than it did on open-class words. However, unlike the open-class results, the impact of sentence context on closed-class words was stable across word positions, suggesting that these syntactic constraints were applied only locally. A second ERP component, distinct from the N400, was elicited primarily by congruent closed-class words.